Formal Debt-Relief, Rescue and Liquidation Options for External Companies in South Africa - A. Boraine (BRICS Law Journal, 2020)
This article discusses how foreign companies doing business in South Africa during periods of financial distress and registered locally as external companies are, as a recent High Court decision confirms, denied the formal debt-relief measures of business rescue and therefore a compromise with creditors because of being excluded by the definition of “company” in the Companies Act 71 of 2008. Nor, for the same reason, may these companies, if solvent, rely on the current liquidation procedures. But they may possibly use the procedure preserved in the otherwise repealed Companies Act 61 of 1973 for liquidation as far as the transitional arrangements in the Companies Act 71 of 2008 allow. The purposive solution suggested in this article for the interplay between the two Acts may need legislative attention. This article surveys other possibilities relevant to these companies such as informal voluntary arrangements, applications for winding-up, ordinary debt collection, and perhaps compulsory sequestration applications. Finally, it raises the policy issue for the legislature to consider why these companies should be denied business rescue and/or a compromise with their creditors when these formal debtrelief measures might help them survive their financial stress and emerge stronger, to the advantage of themselves, their creditors, their stakeholders and communities, and the entire nation. It is submitted that these issues could and should be considered as part of the current law reform process of South African insolvency law.